Implementation of Meta Ads Strategy in Enhancing Customer Engagement on the Instagram Account of PT Tourezia Cakra Inspira - Najwa Nurfadilah; Erlita Ridanasti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the implementation of Meta Ads strategies in enhancing customer engagement. The research was conducted due to the gap between the high reach achieved by the company and the low level of audience interaction or engagement. This study employs a qualitative approach using a narrative analysis method. Data were collected through participant observation during the internship, in-depth interviews, and analysis of campaign performance documents. The results indicate that the implementation of Meta Ads is still highly oriented toward conversion and lead generation, resulting in engagement not being a primary focus. Furthermore, the study reveals a mismatch between audience segmentation (B2B) and the content approach (B2C), which contributes to the low level of audience engagement.